2008
DOI: 10.2495/wm080041
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase pyrolysis modelling of wooden waste

Abstract: Pyrolysis technology has been demonstrated in recent researches as one of the most effective and environmentally friendly methods for solid wastes pretreatment and energy utilization. Pyrolysis is a process wherein organic materials are exposed to thermal treatment in the absence of an oxidizing agent, resulting in a solid (char), liquid (tar and bio-oil) and volatile gases (CO, CO 2 , CH 4 , and H 2 ). A two phase (solid-gas) equilibrium model is proposed in this work in order to simulate the pyrolysis proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…By subjecting the raw biomass to a thermal decomposition process, i.e., pyrolysis, it was possible to obtain the calorific values comparable to other solid fuels such as coal, lignite or wood. Similar calorific values of biochars produced have been reported by other authors, as shown in Table 5 [59][60][61]. The analyses showed no content of total nitrogen in the samples assessed, and the processes of pyrolysis did not produce any change in this parameter.…”
Section: Discussionsupporting
confidence: 88%
“…By subjecting the raw biomass to a thermal decomposition process, i.e., pyrolysis, it was possible to obtain the calorific values comparable to other solid fuels such as coal, lignite or wood. Similar calorific values of biochars produced have been reported by other authors, as shown in Table 5 [59][60][61]. The analyses showed no content of total nitrogen in the samples assessed, and the processes of pyrolysis did not produce any change in this parameter.…”
Section: Discussionsupporting
confidence: 88%
“…During pyrolysis, most unstable matters, such as C containing materials [14] , volatile matter of organic matters [15,16] , and N containing matters [17] could lose, but aromatic compound may be detained [18] and which lead more C content in biochar than raw materials.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, biochar directly carbonized and returned to the field plays an important role in crop growth, soil water storage and fertilizer conservation, improving fertilizer utilization rate, increasing yield and improving quality. The technology of direct carbonization of biochar into fields, whether as an application form of biochar or a new potential form of fertility, is of great significance to the sustainable development of agriculture, the realization of a virtuous cycle of agricultural production and the increase of farmers' production and income [19] .…”
Section: Soil Modificationmentioning
confidence: 99%